Werbung für das Christentum und Häresiographie: die ‚Peraten' und die redaktionelle Gestaltung der Refutatio omnium haeresium des sog. ,Hippolyt von Rom' - Hanstein, Sebastian (Vigiliae Christianae, 2024)
"The study approaches the Refutatio omnium haeresium by "Hippolytus of Rome" from a completely new perspective. It offers a detailed analysis of the genre of the writing, which is identified as a protreptikos, a promotional writing for Christianity. One focus is the elaboration of the intention and working method of its author against the background of the method of authors of the imperial period. It is shown how the author creatively changes and compiles his original sources to suit his needs. Passages through the special material make it likely that it is largely a literary product of the author. This is followed by an extensive study of the so-called Peratics, which combines structural analysis and thorough examination of content"--